Chronic heart failure: modern problems and their solutions - V. S. Nesterov; I. A. Urvantseva; A. S. Vorobev (Лечащий Врач)
Incidence of chronic heart failure among population of different regions of Russian Federation ranges from 7 to 10%. The part of patients with advanced heart failure during 1998–2014 years increased from 4,9% to 8,8%. Importance of prevention and treatment of basic risk factors and cardiac diseases, leading to destabilized cardiac performance, is of great priority. We discuss current problems of diagnostics, medical, non-pharmacological and endovascular treatment of these patients. Also we show possible ways of their solution.